Rozwiąż równania:
a) -3x = 2x - 10
b) 2x - 2 = 7 - x
c) 10 = 4 - 2x
d) -(2x - 1) = 4
e) 2(x + 1) = x
f) 2t - (3t + 1) = 6

Rozwiąż równania:
a) 4x - 3 = 3x + 5
b) 5x + 2 = 7 - 3x
c) 3(x - 1) = 0
d) -6(x + 1) = 24
e) -7(x - 2) = 3x - 1
f) 4(x - 1) = 6(1 + x)

Proszę o rozwiązanie tych działań. :) Z góry dziękuje.

3

Odpowiedzi

Najlepsza Odpowiedź!
  • Kks7
  • Początkujący
2009-11-26T15:10:50+01:00
Zad.1
a) -3x = 2x - 10
-3x-2x = -10
-5x=-10 /: (-5)
x=2

b) 2x - 2 = 7 - x
2x+x=7+2
3x=9 /:3
x=3

c) 10 = 4 - 2x
10-4=-2x
6=-2x /:(-2)
x=-3

d) -(2x - 1) = 4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=-2/3

e) 2(x + 1) = x
2x+2=x
2x-x=-2
x=-2

f) 2t - (3t + 1) = 6
2t-3t-1=6
2t-3t=6+1
-t=7 /*(-1)
t=-7

Zad.2
a) 4x - 3 = 3x + 5
4x-3x=5+3
x=8

b) 5x + 2 = 7 - 3x
5x+3x=7-2
8x=5 /:8
x=5/8

c) 3(x - 1) = 0
3x-3=0
3x=3 /:3
x=3

d) -6(x + 1) = 24
-6x-6=24
-6x=24-6
-6x=18 /:(-6)
x=-3

e) -7(x - 2) = 3x - 1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=15/10

f) 4(x - 1) = 6(1 + x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
1 5 1
2009-11-26T15:22:02+01:00
A)-5x=-10
b)1x=9
c)2x=-6
d)-2x=3
e)x=-2
f)1t=7



a)x=8
b)8x=5
c)3x=3
d)-6x=30
e)-10x=-15
f)-2=10
2009-11-26T15:21:49+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10:(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9:3
x=3
c) 10=4-2x
2x=-10+4
2x=-6:2
x=-3
d) -(2x - 1) = 4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=-2/3
e) 2(x + 1) = x
2x+2=x
2x-x=-2
x=-2
f) 2t - (3t + 1) = 6
2t-3t-1=6
2t-3t=6+1
-t=7 /*(-1)
t=-7

a) 4x - 3 = 3x + 5
4x-3x=5+3
x=8
b) 5x + 2 = 7 - 3x
5x+3x=7-2
8x=5 /:8
x=5/8

c) 3(x - 1) = 0
3x-3=0
3x=3 /:3
x=3
d) -6(x + 1) = 24
-6x-6=24
-6x=24-6
-6x=18 /:(-6)
x=-3
e) -7(x - 2) = 3x - 1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=15/10
f) 4(x - 1) = 6(1 + x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5